Trapping and reactivity of a molecular aluminium oxide ion - Hicks, J; Heilmann, A; Vasko, P; Goicoechea, J; Aldridge, S (Wiley, 2019)
Aluminium oxides constitute an important class of inorganic compound that are widely exploited in the chemical industry as catalysts and catalyst supports. Due to the tendency for such systems to aggregate via Al-O-Al bridges, the synthesis of well-defined, soluble, molecular models for these materials is challenging. Here we show that reactions of the potassium aluminyl complex K2 [(NON)Al]2 (NON=4,5-bis(2,6-diiso-propylanilido)-2,7-di-tert-butyl-9,9-dimethylxanthene) with CO2 , PhNCO and N2 O all proceed via a common aluminium oxide intermediate. This highly reactive species can be trapped by coordination of a THF molecule as the anionic oxide complex [(NON)AlO(THF)]- , which features discrete Al-O bonds and dimerizes in the solid state via weak O⋅⋅⋅K interactions. This species reacts with a range of small molecules including N2 O (to give a hyponitrite ([N2 O2 ]2- ) complex) and H2 , the latter offering an unequivocal example of heterolytic E-H bond cleavage across a main group M-O bond.